Adolescent Men's Pregnancy Resolution Choices in Relation to an Unintended Pregnancy: A Comparative Analysis of Adolescent Men in Three Countries. (August 2013) - Lohan, Maria; Olivari, Maria Giulia; Corkindale, Carolyn; Milani, Luca; Confalonieri, Emanuela; Cruise, Sharon; O'Halloran, Peter; Alderdice, Fiona; Hyde, Abbey
This article investigates adolescent men's pregnancy resolution choices in Australia, Ireland, and Italy. It addresses two main gaps in the literature: the lack of research on (adolescent) men's views on unintended pregnancy and pregnancy resolution and the lack of international comparative case studies on men and reproductive choices. Consistent with theories of the transformation of intimacies in society and the growth of individualization, the results suggest that adolescent men are interested in the effect of an unintended pregnancy on their individual biographies as well as the effect on their girlfriend's health and well-being. However, Australian male adolescents were much more likely to choose abortion than Italian or Irish adolescents, suggesting adolescent males have also internalized country-level debates surrounding abortion. Methodologically, the article demonstrates an innovative approach to data collection using a computer-based interactive drama to facilitate participants' deliberation and responses. It was shown to engage a large number of adolescent men and is likely to have wider generalizability in developing international comparative research on the topic as well as applications for health promotion.